2012
DOI: 10.3109/0284186x.2011.653438
|View full text |Cite
|
Sign up to set email alerts
|

Importance of hemoglobin concentration and its modification for the outcome of head and neck cancer patients treated with radiotherapy

Abstract: In conclusion, low hemoglobin is a significant negative prognostic factor for radiotherapy of head and neck cancer. Correction of pre-treatment low hemoglobin by blood transfusion and/or erythropoietin stimulating agents does, however, not improve the outcome. Smoking leads to a decrease in effective hemoglobin and poorer treatment outcome. Smoking should be avoided in order to improve the therapeutic efficacy of radiotherapy and development of other smoking-related diseases and/or secondary cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 133 publications
5
61
0
Order By: Relevance
“…One of the possible mechanisms involves hypoxia [13,[22][23][24]. Cigarette smoking is associated with increased blood carboxyhemoglobin concentrations, which will cause a leftward shift of the hemoglobin-oxygen dissociation curve [25]. A study in 2008 by Fortin A et al [24] reported that combined exposure of smoking during the radiation and antioxidant vitamin would increase the rate of long-term mortality and recurrence among HNC.…”
Section: Discussionmentioning
confidence: 98%
“…One of the possible mechanisms involves hypoxia [13,[22][23][24]. Cigarette smoking is associated with increased blood carboxyhemoglobin concentrations, which will cause a leftward shift of the hemoglobin-oxygen dissociation curve [25]. A study in 2008 by Fortin A et al [24] reported that combined exposure of smoking during the radiation and antioxidant vitamin would increase the rate of long-term mortality and recurrence among HNC.…”
Section: Discussionmentioning
confidence: 98%
“…Evaluation of the study outcome was limited by the absence of smoking data since smoking affects the efficacy of radiotherapy, and the risk of recurrence [17,33]. The problem was modest, though, since the randomized study setup was likely to have allocated smokers evenly in the two treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Hoff [24], studying the response to radiotherapy in head and neck cancer, considered normal hemoglobin levels to be 12-15 g/dl for women and 13-16 g/dl for men. The optimal hemoglobin level as a prognostic factor has not been definitely established [25].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, smoking was associated with the development of complications only in bivariate analysis, which may be due to the small number of cases analyzed. However, it is worth emphasizing that smoking leads to a reduction in effective hemoglobin and to poorer treatment outcome [24]. …”
Section: Discussionmentioning
confidence: 99%